Digital Storytelling and EFL Students’ Engagement in Developing Speaking Skills - Ramadanti, Nisrina; Ridwan, Iwan; Saefullah, Hilmansyah (IKIP Siliwangi, 2026)
This study aimed to explore the students’ behavioral, cognitive, and emotional engagement in English speaking learning through the digital storytelling (DST) project. This case study research was conducted at a private senior high school in Karawang, West Java. The participants in this study were 14 eleventh-grade students. The data were collected by observation, interview, and students’ reflective journals. Six of the fourteen students voluntarily participated in the interview to obtain their views on the DST project. The results of the study revealed that students showed positive responses in behavioral engagement because they completed their project and constantly paid full attention in class. Secondly, the DST project also cognitively involved the students, both in speaking skills and in using technology. Finally, the students' emotional engagement was positive during this DST project, as they felt happy sharing their hobbies through a digital platform.